Comparison of Mechanical Properties of Cement-Stabilized Loess Produced Using Different Compaction Methods. (7th October 2020) - Jiang, Yingjun; Yuan, Kejia; Li, Qilong; Deng, Changqing; Yi, Yong; Zhang, Yu; Xue, Jinshun
Abstract : Mechanical properties are important indexes to evaluate the improvement effect and engineering performance of cement-stabilized loess (CSL). This paper presents a comparison of the mechanical properties of CSL compacted using hammer quasi-static compaction method (QSCM) and vertical vibration compaction method (VVCM). The compaction properties, unconfined compressive strength (UCS), splitting strength (SPS), and resilient modulus (RM) of the laboratory-compacted CSL using VVCM and QSCM are tested and compared. Furthermore, the effects of compaction method, cement content, compaction coefficient, and curing time of the CSL specimens are investigated. In addition, field measurements are carried out to validate the laboratory investigations. The results show that the laboratory-compacted CSL using VVCM has a larger dry density and smaller optimum water content than that using QSCM. And the compaction method has a great influence on the mechanical strength of CSL. The UCS, SPS, and RM of the specimen produced using VVCM are averagely 1.17 times, 1.49 times, and 1.17 times that of CSL produced using QSCM, respectively, and the UCS, SPS, and RM of the specimens produced using these two methods increase linearly as the cement content and compaction coefficient increase, while the mechanical strength growth curve experiences three periods of increasing sharply, increasing slowly, and stabilizing with the curing time increased. Moreover, the results also show that the mechanical properties of laboratory-compacted CSL using VVCM have a better correlation of 83.8% with the field core samples.